Analysis and health risk assessment of heavy metals in some onion varieties - Nusrat Bibi; Munir H. Shah; Nadeem Khan; Qaisar Mahmood; Ali Abdullah Aldosari; Arshad Mehmood Abbasi (Arabian Journal of Chemistry, 2021)
Being a global concern, the current scenario of food chain contamination is one of the major threats to human health. Unrestrained human population, industrialization, urbanization, and extensive use of agrochemicals are among the major causes of heavy metals (HMs) contamination in the food chain. The present study was intended to quantify some HMs and to evaluate their sources and health risks in different varieties of onion using standard analytical approaches. Overall, nine HMs were quantified in the bulbs and leaves of nine varieties of onion. Ascending order of HMs’ concentration was as follow: Fe > Zn > Mn > Co > Pb > Cu > Cr > Cd > Li (bulbs) and Fe > Mn > Zn > Cu > Cr > Pb > Co > Li > Cd (leaves). Most of the measured levels were found to be relatively higher in the leaves than bulbs. Red Flame (V4), Super Sarhad (V3), Red Orb (V2), White Pearl (V7) and Zeus (V9) varieties showed elevated levels of Cu, Fe, and Zn; Cr and Mn; Co and Pb; Cd and Li, respectively in the bulbs. Likewise, Red Orb (V2) and White Pearl (V7) revealed elevated levels of the metals, while Golden Orb (V6) exhibited relatively lower metal levels. Highly significant positive correlations (≥90% at p ≤ 0.01) were found between Zn-Cu and Zn-Fe (in bulbs) and Cu-Co (in leaves), indicating their common origin. Principle component analysis indicated substantial anthropogenic contamination of the HMs in onion. In addition, hierarchal clustering revealed associations of different varieties based on similarities in the metal levels. The calculated values of health risk index (HRI), target hazard quotient (THQ), hazard index (HI), and target cancer risk (TCR) in the bulbs and leaves of all varieties were within the safe limit for both adults and children. Therefore, human consumption of these onion varieties is considered safe with respect to the HMs. However, currently used remediation approaches should focus on the reduction of health risks associated with HMs contamination in the food crops.